Charge balance for the mesosphere with meteoric dust particles. (May 2015) - Asmus, H.; Robertson, S.; Dickson, S.; Friedrich, M.; Megner, L.
Abstract: An aerosol particle charging model initially developed for noctilucent cloud ice particles has been extended in several steps in order to better explain the data for charged meteoric smoke particles (MSPs) obtained by the nighttime and daytime CHAMPS rockets launched from Andøya, Norway, in October 2011. Addition of photodetachment to the model shows that this process reduces the number density of positively charged MSPs as well as the number density of negatively charged MSPs as a consequence of the photodetached electrons neutralizing the positively charged MSPs. In addition, the model shows that the ionization rate can be deduced from the electron number density and the electron–ion recombination rate only at the highest altitudes (those with ionization rates above 20 cm −3  s −1 ) as a consequence of recombination on the MSPs being dominant at lower altitudes. The differences between the daytime and the nighttime rocket data suggest a photodetachment rate between 0.1 and 0.01 s −1 . A further extension of the model to include the formation of negative ions and their destruction helps explain the ledge seen in the number density of the lightest negatively charged particles. The MSP number densities that are the inputs to the charging model are taken from the CARMA/CHEM2D model. The CHAMPS data are more consistent with number densities generated with an assumed input flux from ablation of 4 t d −1 than with 44 t d −1 assumed previously. Highlights: We model the charging of meteoric smoke particles (MSPs) in the mesosphere. Ionization, recombination, photodetachment and MSP charging are modeled. Inputs include the MSP number density profile from the CARMA/CHEM2D model. Parameters are adjusted to best reproduce data from the CHAMPS rockets. The addition of negative ions to the model significantly improves agreement.